A Brief Analytical Review of the Torah, Psalms and Gospel - Dr. HM Azhar Usama,; Dr. Shaista Jabeen,; Dr. Zill-e-Huma,; Dr. Ayesha khan,; Ayesha Tariq, (Al-Qanṭara, 2023)
This article presents an extensive collection of Torah, Psalms, and Gospels as a research and analytical overview. The style of this research paper will be narrative. By reviewing the literature, it has been found that the study of human history is actually the story of the rise and fall of nations. It is known from authentic sources that in different periods of history, man has been remembering his Lord in one form or another; even today, there is no corner of the world where the traces of religion are extinct. Rather, the renaissance of religion is felt in this century. Today the world is in a state of indecisiveness by adopting all the isms and systems of life and is eager to listen to the divine message to satisfy its heart. This is the reason why religious revival movements are gaining influence in Europe and the Western world. Adherents of the world's leading religions claim to have one or more divine books that describe to some extent the basic teachings of their religion. It is generally said that all religions have good things, moral teachings, so all these religions are correct. The Holy Quran explains the true truth in response to this assumption. "In the beginning, all people were on the same path. (Then this state did not remain and differences arose) Then Allah sent the Prophets who gave good tidings of righteousness and warned of the consequences of unrighteousness, and sent down with them the Book of Truth, so that they might distinguish among people about the truth. Differences had arisen, let him judge them — (and the reason for these differences occurring was not that the people were not told the truth in the beginning. No) the differences were made by those who were given the knowledge of the truth. After following the clear instructions, they left the truth and took different methods simply because they wanted to abuse each other, so those who believed in the Prophets, Allah, by His permission, showed them the way to the truth, about which the people differed. Allah guides whomever He wills. Keywords: Torah, Psalms, Gospel, Analytical Study, Scriptures, Christianity, Judaism, Prophets